Can Trimodal Distribution of HbS Levels in Sickle Cell Traits Be Used To Predict the Associated Alpha-Thalassemia For Screening Cases in Central India? - Bhushan Warpe; AV Shrikhande; SV Poflee (Iranian Society of Pathology, 2016)
Background: Until now, trimodal distribution of HbS has been seen by six different studies in the world when associated with alpha-thalassemia with confirmation by corresponding alpha-genotyping studies. The RBC indices reduce as alpha-globin genes reduce in sickle cell trait (SCT) patients, which decreases the extent of intra-vascular sickling and thus betters the clinical course of the patients. This is a pioneer study conducted on Central Indian poor population to use the already proven six studies to screen associated alpha-thalassemia in SCT patients thus, circumventing the much costlier alpha-genotyping studies. Moreover, it aimed to study the haematological parameters in such cases. Methods: The study was performed at RHDMC, IGGMC, Nagpur, India from 2003 to 2012. The sample population was suspected cases of haemolytic anaemia. CBC and RBC indices were obtained by a cell analyzer. The sickle solubility test positively screened cases were confirmed by agar-gel haemoglobin electrophoresis at pH 8.6. Finally, quantitative assessment of haemoglobin variants was performed by HPLC. Results: Out of total 5819 cases over ten years, 933 cases were sickle heterozygotes. Overall, 180/933 subjects were predicted to be homozygous alpha-thalassemia and 338/933 were heterozygous alpha-thalassemia, based on trimodal distribution of HbS. Conclusion: Genotyping is costlier for majority of the poor non-affording patients in Indian government set-ups, so this study is suitable to screen for associated alpha-thalassemia in SCT patients.